Construction of Learning Diagnostic Tests in the Mathematics Learning Numbers and Numerical Work for Prathomsueksa 6 Student under the Office of Nong Bua Lamphu Primary Educational Service Area Zone 1 - Cormick, Phitchanan Mc; Tayraukham, Assoc. Prof. Dr. Sombat (Journal for Developing the Social and Community, 2019)
The purpose of this research is to improve mathematics achievement is the Mathematics Learning Numbers and Numerical Work for Prathomsueksa 6 Student to analyze the Classical Test Theory and Diagnostic groups and leaning about leaning in Numbers and Numerical Work for Prathomsueksa 6 Student under the Office of Nong Bua Lamphu Primary Educational Service Area Zone 1. The sample of this study comprise from 460 Prathomsueksa 6 students from 32 schools from two semester year 2018. Obtained using the multi-stage random sampling technique. The instrument used in the study was 1) test to investigate defects. To test the proposition is to show students hoe to think and explain why or resolution. They are built by 4 completion of 54 items. 2) The diagnostic first test of 4 choice. They are built by 4 completion of 54 items. 3) Second test for the diagnostic of 4 choice. They are built by 4 completion of 54 items. Which the diagnostic first test and second test to determine the quality of the test. The discrimination. Reliability. And the standard error of measurement. The findings revealed the following : 1. The Construction of Learning Diagnostic Tests in the Mathematics Learning Numbers and Numerical Work for Prathomsueksa 6 to analyze the test quality of Classical Test Theory. The results of the analysis are as follows ; (1) The content validity test to investigate and the Leaning Diagnostic First Test showing congruence indices ranging 0.60 – 1.00. (2) The discrimination of diagnostic first tests and second test of 4 completion in term of discriminative powers ranging 0.28 – 0.71. (3) The reliability of the leaning Diagnostic first test of 4 completion in terms of the reliability were 0.73, 0.66, 0.70, 0.71 and leaning Diagnostic second test of 4 completion in terms of the reliability were 0.60, 0.54, 0.54 and 0.54. (4) The standard error of measurement of the Leaning Diagnostic first test of 4 completion were 2.03, 2.04, 2.07, 2.11 and Leaning Diagnostic second test of 4 completion were 2.46, 2.49, 2.63 and 2.60. The study of defects in the test of a number showed that the most students do not understand the definition of a number and students do not understand the definition of an number are 95.33 and 97.33 percent respectively.